EXPLORING NURSING STUDENTS' LEARNING EXPERIENCE IN COMMUNITY HEALTH NURSING PRACTICE: A PHOTOVOICE STUDY - Israfil, Israfil; Indrayani, Ni Luh Dwi; Suyasa, I Gede Putu Darma; Wulandari, Sarah Kartika; Citra Sari, Ni Made Candra (Universitas Airlangga, 2026)
Introduction: Learning in the community presents different challenges than learning in a clinical setting. However, studies on student nurses' experience in the community have not been discussed comprehensively. This study aimed to explored nursing students’ experiences in a community setting using the five stages of the nursing process Method: This study used a qualitative design with the Photovoice approach. A total of 14 students were involved in the study. Data was collected by taking photos and small group discussions for the narrative photo with the SHOWED approach. Photos and narration are the primary data and are analyzed thematically. Result: A total of approximately eighteen photos have been included. At the assessment phase, the student requires an adaptation process and strategic anticipation, as the practice was conducted directly in the participants’ community. Formulating nursing diagnosis is done through teamwork and group discussion with an approach based on evidence and theory, and asking for guidance from the lecturer as a facilitator for learning. The development of nursing intervention was done with active participation from society, presenting the intervention plan to the community, community meetings, and ensuring the legality of the plan's activities. Implementation in the nursing community is implemented collaboratively between students and the community following the agreed-upon plan. Evaluating nursing practice is done with collaborative reflection of students, discussion together, and related plans, actions, and carrying on independently in public. Conclusion: This study finds that community-based nursing practice requires student adaptation, strategic planning, and evidence-based teamwork. Keywords: Clinical nursing education, community health nursing, photovoice, nursing students, nursing care plan